Quand les femmes s'en mêlent : genre et pouvoir - Bard, Christine; Baudelot, Christian; Mossuz-Lavau, Janine (Éditions de La Martinière, 2004)
C'est dans les années 1970 que des anthropologues féministes américaines, réfléchissant aux rapports de pouvoir entre hommes et femmes, ont intronisé le mot " genre " : elles faisaient ainsi référence au rôle social des uns et des autres, par opposition au sexe biologique, pour montrer que la place des femmes et des hommes dans la société est avant tout le produit d'une culture. Simone de Beauvoir l'avait déjà dit avec d'autres mots : " On ne naît pas femme, on le devient. " Au moment même où la hiérarchie traditionnelle des sexes était remise en cause, des chercheuses et des chercheurs en sciences sociales reprirent le concept et sapèrent ainsi l'idée que la domination masculine était " naturelle ". Depuis, le principe de l'égalité entre les droits de l'homme et les droits de la femme a fait son chemin. Mais le principe est-il devenu réalité ? Les historien(ne)s, sociologues, politologues que réunit ce livre font un bilan : quand les femmes s'en mêlent, qu'il s'agisse de la vie publique ou de la vie privée, les inégalités demeurent, ou se transforment, comme si un pas en avant sur la voie de l'égalité déclenchait deux pas en arrière. En politique, parité ne signifie toujours pas égalité. Dans le monde du travail, les femmes sont plus frappées par le chômage, alors qu'elles sont plus nombreuses à l'Université. Pourquoi tant de femmes qui veulent accéder à des postes de responsabilité échouent-elles à traverser le plafond de verre ? Et pourquoi du sexisme ordinaire au viol, les violences à l'encontre des femmes sont-elles si fréquentes ?
Keywords: approches et analyses; cycles supérieurs; fem9000; genre; identités LGBTQIA2+; identités de genre; interdisciplinarité; inégalités; systèmes d'oppression; thématiques; travail; violences

Precarious life: The powers of mourning and violence - Butler, Judith (Verso, 2004)
Responding to the US’s perpetual war, Butler explores how mourning could inspire solidarity.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; corps; discipline; guerre; histoire et politique; médias; philosophie; périodes historiques; régions géographiques; sciences humaines; sofia; thématiques; violences; états-unis; éthique

Pour une théorie générale de l'exploitation. Deuxième partie: repartir du bon pied - Delphy, Christine (Mouvements, 2004)
Keywords: OFDIG; afrique; amériques; approches et analyses; asie; discipline; discours dominant; exploitation; intersectionnalité; marxisme; ressource en ligne; régions géographiques; systèmes d'oppression; thématiques; travail; violences; économie; économie sociale

No future: Queer theory and the death drive - Edelman, Lee (Duke University Press., 2004)
In this searing polemic, Lee Edelman outlines a radically uncompromising new ethics of queer theory. His main target is the all-pervasive figure of the child, which he reads as the linchpin of our universal politics of “reproductive futurism.” Edelman argues that the child, understood as innocence in need of protection, represents the possibility of the future against which the queer is positioned as the embodiment of a relentlessly narcissistic, antisocial, and future-negating drive. He boldly insists that the efficacy of queerness lies in its very willingness to embrace this refusal of the social and political order. In No Future, Edelman urges queers to abandon the stance of accommodation and accede to their status as figures for the force of a negativity that he links with irony, jouissance, and, ultimately, the death drive itself. Closely engaging with literary texts, Edelman makes a compelling case for imagining Scrooge without Tiny Tim and Silas Marner without little Eppie. Looking to Alfred Hitchcock’s films, he embraces two of the director’s most notorious creations: the sadistic Leonard of North by Northwest, who steps on the hand that holds the couple precariously above the abyss, and the terrifying title figures of The Birds, with their predilection for children. Edelman enlarges the reach of contemporary psychoanalytic theory as he brings it to bear not only on works of literature and film but also on such current political flashpoints as gay marriage and gay parenting. Throwing down the theoretical gauntlet, No Future reimagines queerness with a passion certain to spark an equally impassioned debate among its readers
Keywords: amériques; approches et analyses; cinéma; communications; discipline; fem1000; premier cycle; psychanalyse; queer; régions géographiques; thématiques; violences; états-unis; études culturelles

Aberrations in Black: Toward a queer of color critique - Ferguson, Roderick A. (Critical American studies series, 2004)
A hard-hitting look at the regulation of sexual difference and its role in circumscribing African American culture. The sociology of race relations in America typically describes an intersection of poverty, race, and economic discrimination. But what is missing from the picture—sexual difference—can be as instructive as what is present. In this ambitious work, Roderick A. Ferguson reveals how the discourses of sexuality are used to articulate theories of racial difference in the field of sociology.
Keywords: amériques; approches et analyses; discipline; fem1000; identités LGBTQIA2+; premier cycle; queer; queer of color; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; violences; états-unis

Gender, discourse, and desire in twentieth-century Brazilian women's literature - Pinto, Cristina Ferreira (Purdue studies in Romance literatures, 2004)
This study by Cristina Ferreira-Pinto explores the poetic and narrative strategies twentieth-century Brazilian women writers use to achieve new forms of representation of the female body, sexuality, and desire. Female writers discussed include: Gilka Machado, Lygia Fagundes Telles, Marcia Denser, and Marina Colasanti. While creating new forms, these writers are also deconstructing cultural myths of femininity and female behavior. In order to understand these myths, the book also presents new readings of some male-authored canonical novels by Jose de Alencar, Machado de Assis, Manuel Antonio de Almeida, and Aluisio Azevedo. The specific focus on female sexuality and desire acknowledges the intrinsic link between sexuality and an individual's sense of identity, and its importance for female identity, given the historical repression of women's bodies and the double standard of morality still pervasive in many Western cultures. In the discussion of the strategies Brazilian female poets and fiction writers employ, Ferreira-Pinto addresses some social and cultural issues that relate to a woman's sense of her own body and sexuality: the characterization of women based on racial features and class hierarchy; marriage; motherhood; the silencing of the lesbian subject; and aging. Ferreira-Pinto's analysis is informed by the works of various and diverse critics and theoreticians, among them Helene Cixous, Teresa De Lauretis, Adrienne Rich, Gloria Anzaldua, Georges Bataille, and Wilhelm Reich.
Keywords: amériques; arts; brésil; corps; discipline; histoire et politique; littérature; maternité; ressource en ligne; régions géographiques; sexualité; thématiques; violences; écriture des femmes*; études littéraires